The plight to dissent: professional integrity and ethical perception in the institutional care work of early childhood educators - Ribers, Bjørn (European Early Childhood Education Research Journal, 2018)
A Code of Ethics for Early Childhood Educators has been established in Denmark, accentuating the development of a professional ethos. However, the divergence between professional ethical ideals and the complex realities of professional practice can result in the phenomenon defined as moral distress. This article is a case study that discloses how moral distress can be processed through ethics education, based on results from an empirical study of early childhood educators’ experiences with moral dilemmas and ethical intervention in institutional care work. The author discusses professionals’ ‘plight to dissent’ when confronting unethical practice. The article concludes that educational programmes based on a supervision method, conceptualised as Ethical Circles (EC), can support early childhood educators to develop ethical perception and professional integrity. Professionals learn to reflect upon the complexities of early childhood education and care, and develop the competency to intervene in unethical practice, when needed, with the aim of putting children first.
Publisher: Routledge _eprint: https://doi.org/10.1080/1350293X.2018.1533707